PROFIL SUHU DAN TEKANAN DARAH PENERIMA VAKSIN BOOSTER COVID-19 DI SENTRA VAKSIN UNTAR (Jurnal Bakti Masyarakat Indonesia, 2022)
The SARS-CoV-2 virus has experienced thousands of mutations and has led to the emergence of new, relatively more dangerous variants. Analysis results of several patients who were hospitalized in the period January - February 2022 showed that most of the patients who died had not been fully vaccinated. Results of the study showed a decrease in antibodies 6 months after the complete primary dose of COVID-19 vaccination, so booster dose was needed to increase individual protection. The implementation of education at Universitas Tarumanagara (UNTAR), especially medical faculty, requires face-to-face hands-on learning activities so that all components involved in these activities need to get booster vaccinations for protection. UNTAR in collaboration with health institution held community service activities in the form of giving booster vaccinations to support government programs, as well as launching academic activities. Blood pressure (< 180/110 mmHg) and temperature (